Specific cell’s nuclei DNA content and cellular heterogeneity of colon adenocarcinoma - A. N. Grabovoy; S. A. Antoniuk; V. P. Silchenko; E. A. Vorobiei; T. M. Savchin (Patologìâ)
Definition of properties and fine pathogenesis mechanisms is a direct condition for improving the effectiveness of the fight against cancer, including colon cancer. Aim. In order to assess the cellular composition heterogeneity of colon adenocarcinoma (AC) on the specific DNA content in the cells’ nuclei 141 biopsies were studied using histological, histochemical, morphological, densitometric and mathematical methods. Methods and results. It was established that in AC with grade increase (G) there is an increase in the relative proportion of cells with nuclei which are most appropriate for functional activity and vice versa. Conclusion. This suggests that AC cellular heterogeneity is not linear, and the function approximates to the parabolic one.